Tuina therapy plus resistance exercise vs. Tuina alone for mechanical neck pain: a randomized controlled trial - Zheng, San; Wu, Zhiwei; Chang, Yaping; Xing, Hua; Shan, Yiming; Fu, Yangyang; Li, Yazhou; Kang, Zhiran; Chen, Jintian; Li, Jiangshan; Li, Jie; Wang, Junliang; et al. (Frontiers in Medicine, 2026)
BackgroundTuina and exercise therapy are widely used to treat mechanical neck pain (MNP), but evidence on their combined efficacy remains limited. This study evaluated the effectiveness of Tuina combined with resistance exercise (RE) versus Tuina alone in managing MNP.MethodsWe conducted a 4-week, analyst-blinded, randomized controlled trial with 90 participants with MNP. Participants were randomly assigned to receive either Tuina Therapy plus RE (TTRE, n = 45) or Tuina alone (n = 45). Both groups underwent two Tuina sessions per week for 4 weeks (eight sessions in total). In addition, the TTRE group performed RE three times daily for 4 weeks. Each RE consisted of 5 s of static resistance followed by 2 s of relaxation. The number of repetitions per session increased progressively: 5 in week 1, 10 in week 2, 15 in week 3, and 20 in week 4. The primary outcome was the change in pain visual analog scale (VAS) score from baseline to week 4. Secondary outcomes included the Neck Disability Index (NDI) score, peak strength of cervical muscle (PSCM), cervical range of motion (CROM), cervical curvature (Cobb Angle), and adverse events.ResultsThe mean age of the 90 enrolled patients was 26.4 years [standard deviation (SD), 3.1 and 49 (54.4%) were female]. The mean difference in VAS scores from baseline at week 4 for TTRE group was −4.2 (95% CI, −4.4 to −4.0). At week 4, the difference in VAS score was 0.5(95% CI, 0.30 to 0.77; p < 0.001) between Tuina group and TTRE group.ConclusionIn this study, participants with MNP in the TTRE group showed statistically greater improvements than those in the Tuina group in pain reduction, functional recovery, extension PSCM, and flexion CROM at week 4. TTRE may be considered a valuable option in the management of MNP.Clinical trial registrationWe registered the trial with the Chinese Clinical Trial Registry (ChiCTR2300068344; Registration Date: February 15, 2023) at http://www.chictr.org.cn.